Modeling and Experimental Study on Air-Gap Membrane Distillation - Lu, Yanyue; Liao, Anping (Asian Journal of Chemistry, 2013)
Membrane distillation (MD) is an attractive separation process compared to the traditional separation processes such as distillation or reverse osmosis. Requiring lower operation temperature and being able to use low-grade thermal energy are the major features of membrane distillation. Membrane distillation can be classified into four configurations. Air gap membrane distillation (AGMD) is one of the most versatile membrane distillation configurations which can be applied to almost any applications. The model of air gap membrane distillation module is established in this paper based on the mechanism of heat and mass transfer. The outlet temperature of hot feed stream and cold stream can be predicted by this model. Thereafter the design of air gap membrane distillation system can be achieved based on the presented module model. Many experiments have been done to validate the rationality of the model.